Notification of brain death in the hospital - Bruna Soares de Jesus Souza; Gerlene Grudka Lira; Rachel Mola (Rev Rene)
Objective: to identifying brain death in the hospital. Methods: it is a cross sectional and quantitative study which analyzed secondary data extracted from the notified brain death registers and from the medical records of the eligible patients. The data were processed and analyzed through descriptive statistics and comparisons. Results: of the 64 cases of notifications, the male gender predominated (67.2%) within the age range from 40 to 59 years (64.1%). There was a greater proportion (71.8%) of causes of death related to Hemorrhagic Cerebral Vascular Accident and Traumatic Brain Injury caused by motorcycle accident, showing statistically significant difference (p<0.05) regarding the gender, age and location. Conclusion: the Hemorrhagic Cerebral Vascular Accident was the most prevalent cause of notification of brain death and the Intensive Therapy Unit was the most notified venue.